Public education COVID-19: Membekalkan nature of science konteks COVID-19 sebagai bahan pembelajaran bagi guru SMPN 08 Rejang Lebong - Euis Nursaadah; Aceng Ruyani; Henny Johan (Riau Journal of Empowerment, 2022)
Integrating science concepts with real contexts, including the COVID-19 context, is essential in the learning process to become meaningful. As one of the public education, schools are expected to provide students with generic skills on dealing with a pandemic using the concepts learned at school. Training on integrating science concepts with real contexts in learning was carried out to teachers and students at Junior High School 08 Rejang Lebong, Bengkulu Province, Indonesia. Training was conducted through ICARE (Introduction, Connection, Application, Reflection, and Extend). The results show that teachers can integrate science concepts with the COVID-19 context. These concepts are respiratory organs, blood cells, antibodies, vaccines, and healthy life. After the activity, the teacher designed science lessons plan to integrate concepts with the previously discussed context. It is hoped that the science learning carried out will be meaningful so that students no longer feel bored participating in learning, especially online learning.